KEANEKARAGAMAN DAN SEBARAN SERANGGA DI KAWASAN PULAU-PULAU KECIL TAMAN NASIONAL KARIMUNJAWA - Erniwati, Erniwati (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Study on diversity and distribution of insects was conducted in seven small islands of Karimunjawa National Park. Central Java from March 24 to April 7, 2006. using two collection methods i.e. pitfall traps and sweeping nets. The study collected 108 species of insects from the seven small islands included 9 ordo of 44 families. They were Lepidoptera (27 species), Odonata (7 species).Orthoptera (8 species). Mantodea (2 species). Blattodea (9 species). Hymenoptera (20 species). Diptera (8 species), Coleoptera (12 species) and Hemiptera (15 species). The highest number of species was collected from Karimunjawa Island (96 species), while other islands were low: denting (30 species).Kumbang (23 species).Kembar (26 species), Nyamiik (56 species). Parang (50 species) and Bengkuang (23 species).Base on fuction on nature, these insects could be divided into phytophagous, pollinator, decomposer, pasitoid, vector and unknown.Three species of butterflies were rediscovered during this study - they were Euploea crameri karimondjawensis.Euploea syhesier karimondjawana and Idea leitconoee karimondjawae. while one species Neplis columelle karimondjawae has not been found yet. Shannon. Simpsons, and Fishers Alpha indexes, and similarity of Jackard to compare the difference among the islands is disccussed.